Comparative analysis of pulmonary function in children born preterm and full-term at 6–9 years of age - Gonzaga,Ana Damaris (2023)
Abstract Objective: To compare pulmonary function parameters and the prevalence of altered pulmonary function in children born preterm and full-term, using the Global Lung Initiative reference values. Methods: This is a cross-sectional study with 6–9-year-old children submitted to measurement of airway resistance (Rint) and spirometry according to the American Thoracic Society and European Respiratory Society Technical Statement. The inclusion criteria were, among the preterm group: gestational age <37 weeks and birth weight <2000g; among the full-term group: schoolchildren born full-term with birth weight >2500g, recruited at two public schools in São Paulo, Brazil, matched by sex and age with the preterm group. As exclusion criteria, congenital malformations, cognitive deficit, and respiratory problems in the past 15 days were considered. Results: A total of 112 children were included in each group. Preterm children had gestational age of 30.8±2.8 weeks and birth weight of 1349±334g. Among them, 46.6% were boys, 46.4% presented respiratory distress syndrome, 19.6% bronchopulmonary dysplasia, and 65.2% were submitted to mechanical ventilation in the neonatal unit. At study entry, both groups were similar in age and anthropometric parameters. Parameters of pulmonary function (Z scores) in preterm and full-term groups were: Rint (0.13±2.24 vs. -1.02±1.29; p<0.001); forced vital capacity (FVC) (-0.39±1.27 vs. -0.15±1.03; p=0.106), forced expiratory volume in one second (FEV1)/FVC (-0.23±1.22 vs. 0.14±1.11; p=0.003), FEV1 (-0.48±1.29 vs. -0.04±1.08; p=0.071), and forced expiratory flow between 25% and 75% of vital capacity (FEF25-75) (1.16±1.37 vs. 2.08±1.26; p=0.005), respectively. The prevalence values of altered airway resistance (16.1 vs. 1.8%; p<0.001) and spirometry (26.8 vs. 13.4%, p=0.012) were higher in preterm infants than in full-term ones. Conclusions: Preterm children had higher prevalence of altered pulmonary function, higher Z scores of airway resistance, and lower Z scores of FEV1/FVC and FEF25-75 compared with those born full-term.